2019
DOI: 10.1177/0046958018825191
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Quality and Financial Performance: Is There a Business Case for Quality?

Abstract: This study examines the relationship between nursing home quality and financial performance to assess whether there is a business case for quality. Secondary data sources included the Online Survey Certification and Reporting (OSCAR), Certification and Survey Provider Enhanced Reporting (CASPER), Medicare Cost Reports, Minimum Data Set (MDS 2.0), Area Resource File (ARF), and LTCFocus for all free-standing, nongovernment nursing homes for 2000 to 2014. Data were analyzed using panel data linear regression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 41 publications
1
40
1
Order By: Relevance
“…Even before the pandemic, NHs were reliant on higher margin Medicare residents to provide financial cushion to invest in staff and quality. 42 Indeed, NHs with higher Medicare prevalence were less likely to suffer staff shortages. Securing the financial health of NHs that allows them to address these staff shortages needs to be a priority that might help NHs ensure that fewer residents are exposed to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the pandemic, NHs were reliant on higher margin Medicare residents to provide financial cushion to invest in staff and quality. 42 Indeed, NHs with higher Medicare prevalence were less likely to suffer staff shortages. Securing the financial health of NHs that allows them to address these staff shortages needs to be a priority that might help NHs ensure that fewer residents are exposed to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…16 Another study found that investing in quality is profitable for nursing homes. 22 There is also evidence that nursing homes that perform better in terms of health outcomes such as pressure ulcers are able to lower costs and ultimately improve their profit margins. 23 Our findings have important implications for policy.…”
Section: Discussionmentioning
confidence: 99%
“…As Weech-Maldonado et al 26 noted, improved quality in NHs, achieved through innovative or efficient care processes, may result in fewer defects and/or avoidable complications, which, in turn, will lower the amount of waste or rework, thereby reducing the costs of delivering care. However, there is the need of a detailed understanding of the relationship between quality and efficiency performance due to the twin challenge of delivering high-quality care while retaining efficiency sustainability.…”
Section: Discussionmentioning
confidence: 99%